Potential and Optimization of Waqf Land Empowerment in South Tapanuli Regency - Damri Batubara; Windari Windari; Abdul Nasser Hasibuan; Annida Karima Sovia (AL-FALAH : Journal of Islamic Economics, 2021)
Purpose: This paper discusses about maximization the land    waqf assets of south Tapanuli Regency reached an area of 108.07 (Ha) with a total of 411 land waqf assets,both certified and uncertified, but the condition did not develop all. Meanwhile, the mandate of the law of the republic of Indonesia number 41 of 2004 in articles 42-43 emphasizes that nazir is obliged to manage and develop waqf assets in accordance with their objectives, functions and designations with sharia principles cerried out productively.Design/Method/Approach: This research is a qualitative research with descriptive method. The subjects were waqf land asset, nazir and nazir institutions of waqf land assets in south Tapanuli regency. The population is 411 and the sample is 20 %. Data collection techniques in the form of observation, interview documentation and literature review.Findings: From this study we found thatthe potential of human resources of land waqf assets has great potential in managing and empowering land waqf assets, but this potential is not optimally empowered because of the unsupportive perception of nazir, lack of responsibility, passed away, relocation, and did not implement his duties as nazir and waqf land assets are idle. The another obstacle are financial capital that is not supported, nazir’s salary is not clear and  does not have an entrepreneurial spirit (such as creative spirit, innovation, skills in empowering waqf land assets).Originality/Values: understand nazir that the importance of land waqf is productively empowered